Carbon nanotubes and graphene as counter electrodes in dye-sensitized solar cells - Simon Bbumba; Moses Kigozi; Ibrahim Karume; Solomon Yiga; Hussein Kisiki Nsamba; Muhammad Ntale (Discover Nano)
Abstract Addressing the global demand for cost-effective and sustainable energy sources, dye-sensitized solar cells (DSSCs) have emerged as a promising alternative to conventional silicon-based photovoltaics. However, the use of platinum which is a rare and expensive counter electrode (CE) hinders the widespread application of DSSCs, necessitating the use of cheap, abundant, and efficient materials. The review therefore focuses on carbon-based nanomaterials specifically carbon nanotubes (CNTs) and graphene as CEs in DSSCs. The CE plays a vital role in regenerating the redox couple, and its charge transfer resistance (Rct) should ideally be 1 Ω cm² for optimal performance. Carbon nanotubes comprising single-walled carbon nanotubes (SWCNTs), double-walled carbon nanotubes (DWCNTs), and multiwalled carbon nanotubes (MWCNTs) are mainly prepared by chemical vapor deposition (CVD). The SWCNTs have achieved an efficiency of 7.79%, comparable to platinum electrodes, and this was due to the morphology, which influenced the redox mediator regeneration but also reduced the Rct. In addition, graphene with high transparency (97.7%), large specific surface area (2630 m2 g− 1), excellent thermal conductivity (3000 W m− 1 K− 1), and good carrier mobility properties (10,000 cm2 V− 1 S− 1) have also been applied. In this, the Graphene nanosheets demonstrated a 6.81% efficiency, comparable to platinum (7.59%) due to a high open circuit voltage (Voc), which accounts for the reduction of iodide/triiodide redox couple. Lastly, the Graphene nanoplatelets demonstrated a 9.3% efficiency comparable to that of Platinum 7.53% due to low charge transfer resistance, high electrocatalytic activity, and good fill factor.